A graça como ponto de partida da unidade entre os cristãos - Santana, Walter Amaral de (2018)
This research seeks to discuss the theme "Grace as the starting point of unity among Christians", in view of the conflicting moment in which the world, people and religions live. In the first chapter we seek to demonstrate a path that can transform the life of the human being and consequently the world through the power of saving grace, given by God to all regardless of their language or religion culture, since we are all made in the image of the Creator. In the second chapter we try to demonstrate the life of the Apostle Paulo, his initial trajectory and the change that occurred in his life after his encounter with the Christ on the road to Damascus and how grace had a special participation in that event. In the third chapter, we will walk to a new period of grace and how it was during the Patristic period through the life of St. Agostinho and how grace comes to be conceptualized by this holy man of God. We will make a trajectory of grace through the Scholastic period, focusing in particular on the life and performance of St. Tomás de Aquino and how grace marked this period. In the fourth chapter we will deal with grace in the Reformation and how it acted in the life of Martinho Lutero and the transformations that occurred in that period through thinkers such as Calvino and Armínio, both for the Protestant Churches as well as for the Roman Catholic Church, we will also reflect on grace in mo dernity in the sense of unity among christians.